Effects of stress of the endoplasmic reticulum on genome-wide gene expression in the bovine liver cell model BFH12 - Bajrami, Eron; Wen, Gaiping; Grundmann, Sarah M.; Ringseis, Robert; Gessner, Denise K.; Eder, Klaus; Justus Liebig University Giessen (My University, 2025)
Previous studies have demonstrated that high-yielding dairy cows experience endoplasmic reticulum (ER) stress in the liver during early lactation. To date, most insights into the role of ER stress in metabolism and disease pathophysiology have been derived from rodent and human models. In dairy cattle, however, the specific impact of ER stress on metabolic pathways and its contribution to disease development remain insufficiently characterized. The objective of this study was therefore to investigate the molecular effects of ER stress using a bovine liver cell model (BFH12 cells). ER stress was induced by incubation with Tunicamycin (TM) and Thapsigargin (TG). Molecular responses to ER stress were assessed via a whole-genome array analysis and PCR targeting genes involved in selected metabolic pathways. Incubation with both ER stress inducers resulted in a marked upregulation of genes associated with the unfolded protein response (UPR) within a 4 to 24-h time frame, indicative of the production of robust ER stress in these cells. Unexpectedly, treatment with TM led to a downregulation of numerous genes involved in lipid biosynthesis, including those related to lipogenesis and cholesterol synthesis. Furthermore, incubation with TM and TG induced upregulation of genes involved in fatty acid oxidation and was accompanied by a reduction in intracellular triglyceride concentrations. Genes associated with inflammatory responses were upregulated by both TM and TG, whereas genes encoding antioxidant enzymes were downregulated. Genes involved in ketogenesis did not exhibit a consistent pattern of regulation. Overall, several effects of ER stress previously described in rodent models could not be replicated in this bovine liver cell system. Extrapolating these findings to dairy cows suggests that while ER stress may contribute to hepatic inflammation, it is unlikely to play a significant role in the development of hepatic lipidosis or ketosis.
Keywords: ddc:640; ddc:360